Prenatal ultrasound diagnosis of holoprosencephaly and associated anomalies. (25th September 2012) - Chaudhari, Hemang D; Thakkar, Gurudatt; Darji, Parth; Khokhani, Pratik
Abstract : Holoprosencephaly is a rare spectrum of cerebral and facial malformations resulting from incomplete division of the embryonic forebrain (prosencephalon) into distinct lateral cerebral hemisphere. Holoprosencephaly spectrum in the fetus is often associated with other anomalies, particularly of the face and extremities. Here we present three different cases of patients with holoprosencephaly who failed to attain routine sonography during 11–20 weeks owing to some unavoidable circumstances. Two of them were diagnosed during the third trimester and one in the late second trimester. Ultrasound findings of associated anomalies were confirmed after a clinical examination of the delivered fetuses.